Aktivitas Public Relations Dalam Menerapkan Budaya Perusahaan - Femi Oktaviani (Expose: Jurnal Ilmu Komunikasi, 2021)
Public relations (PR) has an essential role in a company, as in the banking world is needed in facing banking competition that is so competitive. Corporate culture in a company is directed to support the strategy and long-term business development to have higher endurance and competitiveness. Public relations are necessary for implementing corporate culture because culture is the foundation in managing a company and supporting a company to achieve optimal performance. This study aims to determine the form of PR commitment and PR activities in implementing corporate culture. This research is qualitative research using a case study approach. The results obtained are a form of commitment consisting of affective commitment by the go spirit and commitment to building teamwork. Then normative commitment consists of an agent of trust (professionalism, respect, integrity, trust, and agent of development), which is implemented through cultural values of innovation and agent of service. The challenges faced by PR in implementing corporate culture are personal culture, customers or partners' challenges, and inter-division team building that has different roles and functions.Keywords: Public Relations, Corporate, Culture.